1983
DOI: 10.1152/jappl.1983.55.3.830
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fasting on glycogen depletion in rats during exercise

Abstract: We recently observed that a 24-h fasted group of rats could run longer than an ad libitum fed control group before becoming exhausted. Because of the demonstrated importance of glycogen levels and free fatty acid availability during endurance exercise, we have investigated several parameters of carbohydrate and lipid metabolism in exercised and nonexercised rats that were either fed ad libitum or fasted for 24 h. A 24-h fast depleted liver glycogen, lowered plasma glucose concentration, decreased muscle glycog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1
2

Year Published

1985
1985
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 0 publications
4
40
1
2
Order By: Relevance
“…Exercise caused less, if any, glycogen depletion in red muscles of 48 h-starved rats than it did in fed controls, in keeping with the findings of others (Dohm et al, 1983). Pre-exercise glycogen contents were lower in the starved group, however.…”
supporting
confidence: 90%
“…Exercise caused less, if any, glycogen depletion in red muscles of 48 h-starved rats than it did in fed controls, in keeping with the findings of others (Dohm et al, 1983). Pre-exercise glycogen contents were lower in the starved group, however.…”
supporting
confidence: 90%
“…Wilber (1959) reported that severe depletion of liver glycogen was noted in all guinea pigs that swam to exhaustion. Liver glycogen depletion might be an important factor in the development of fatigue because as liver glycogen is depleted during exercise there is an inability to maintain blood glucose level, and the ensuing hypoglycemia could result in impaired nervous function (Dohm et al, 1983). Dohm et al (1983) also demonstrated the importance of muscle glycogen levels in endurance exercise and suggested that depletion of muscle glycogen was a factor in fatigue and exhaustion (Jung et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Liver glycogen and muscle glycogen levels depletion might be an important factor in the development of fatigue because as glycogen is depleted during high-intensity exercise, then there is an inability to maintain blood glucose level, which result in fatigue and exhaustion. 22) Results from this study showed that mice in 1-BCP groups significantly increased their liver glycogen and muscle glycogen levels, compared with control group, indicating 1-BCP enhance the exercise endurance may owing to increased the storage of liver glycogen. Moreover, there is a dose-dependent effect between 1-BCP-H and 1-BCP-L (p<0.05), which is another confirmation that 1-BCP has the anti-fatigue effects.…”
Section: )mentioning
confidence: 60%